2017
DOI: 10.5897/jmpr2017.6405
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of essential oils for preventive or curative management of melon gummy stem blight and plant toxicity

Abstract: Melon cultivation is frequently heavily reliant on synthetic fungicides, including products used to control gummy stem blight caused by Stagonosporopsis cucurbitacearum. The essential oils used in controlling plant pathogens may offer an alternative to chemical pesticides. This study evaluated the effectiveness of essential oils to control the gummy stem blight in melon plants. In vitro tests were carried out using essential oils obtained from ripe noni fruit (Morinda citrifolia) and dehydrated leaves of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
0
7
0
2
Order By: Relevance
“…Naveenkumar et al [54] reported that for Oryza sativa (rice) seedlings, a C. citratus essential oil increased the seed germination, shoot length, root length, and vigor. Also, a C. citratus essential oil was shown to reduce the severity of S. cucurbitacearum infections in melon plants [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Naveenkumar et al [54] reported that for Oryza sativa (rice) seedlings, a C. citratus essential oil increased the seed germination, shoot length, root length, and vigor. Also, a C. citratus essential oil was shown to reduce the severity of S. cucurbitacearum infections in melon plants [34].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, lemongrass essential oil (Cymbopogon citratus) was shown to provide 100% inhibition of mycelial growth of S. cucurbitacearum [22,33]. Moreover, Dalcin et al [34] reported that treatment with a low concentration of lemongrass essential oil (<0.3%) reduced the severity of S. cucurbitacearum infections in melon plants.…”
Section: Introductionmentioning
confidence: 99%
“…As for noni essential oil, the literature has highlighted the antimicrobial effects of M. citrifolia against various pathogens, such as Aspergillus niger, A. fumigatus, Curvularia sp., Helminthosporium sp., Olivea neotectone, Pseudomonas sp., Rhizopus oryzae, Sclerotium sp. and Stagonosporopsis cucurbitacearum [22,23,42,42,43]. Even though in some cases noni essential oil had a toxic effect on seeds [22], fungal inhibition was proportional to the increase in concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…They are plant origin volatile components naturally occurring and have strong antimicrobial and antioxidant potential (Prakash et al, 2015). The phytopathogenic fungi control with essential oils has been showing efficiency in studies carried out in several cultures, such as maize (Mourão et al, 2017), melon (Dalcin et al, 2017), bean plant (Hillen et al, 2012), tomato plant (Santos Neto et al, 2016), among others. Among the works carried out, can stand out the studies by Dalcin et al (2017), Silva et al (2017) and Osorio et al (2018) with noni (M. citrifolia L.).…”
Section: Introductionmentioning
confidence: 99%
“…The phytopathogenic fungi control with essential oils has been showing efficiency in studies carried out in several cultures, such as maize (Mourão et al, 2017), melon (Dalcin et al, 2017), bean plant (Hillen et al, 2012), tomato plant (Santos Neto et al, 2016), among others. Among the works carried out, can stand out the studies by Dalcin et al (2017), Silva et al (2017) and Osorio et al (2018) with noni (M. citrifolia L.). The plant contains phytochemicals with antibacterial, antiviral, antifungal, antitumor, anthelmintic, analgesic, hypotensive, anti-inflammatory and immunological effects.…”
Section: Introductionmentioning
confidence: 99%